Innovating state budget management to unlock resources and drive socio-economic development - Le Hung Son; Nguyen Huu Trieu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
The State Budget Law serves as a regulatory framework for maintaining a proactive and stable balance of the state budget through the alignment of revenue and expenditure. It plays a pivotal role in regulating the nation’s monetary inflows and outflows, thereby reinforcing and enhancing the position and function of financial and budgetary operations. This contributes to economic stability and growth, facilitates economic restructuring, and enables more effective solutions to social welfare issues, poverty reduction, and ensures national defence security, foreign affairs tasks, as well as timely responses to emerging challenges. Moreover, the State Budget Law ensures improved quality, efficiency, and proactivity in the management and administration of the state budget. It also promotes administrative reform in budget management and enhances budget transparency. Therefore, the amendment and supplementation of the State Budget Law, aimed at innovating budget management, will help unlock resources and create momentum for socio-economic development. Code: 20052801